Reactive power planning under conditional-value-at-risk assessment using chance-constrained optimisation - López, Julio [UNESP]; Contreras, Javier; Mantovani, Jose R. S. [UNESP] (Inst Engineering Technology-iet, 2015)
This study presents a risk-assessment approach to the reactive power planning problem. Chance-constrained programming is used to model the random equivalent availability of existing reactive power sources for a given confidence level. Load shedding because of random equivalent availability of those reactive power sources is implemented through conditional-value-at-risk. Tap settings of under-load tap-changing transformers are considered as integer variables. Active and reactive demands are considered as probability distribution functions. The proposed mathematical formulation is a two-stage stochastic, multi-period mixed-integer convex model. The tradeoff between risk mitigation and investment cost minimisation is analysed. The proposed methodology is applied to the CIGRE-32 electric power system, using the optimisation solver CPLEX in AMPL.
Keywords: Risk management; Load shedding; Power transformers; Minimisation; Investment; Reactive power planning; Conditional-value-at-risk assessment; Chance-constrained optimisation; Chance-constrained programming; Random equivalent availability; Reactive power sources; Confidence level; Under-load tap-changing transformers; Integer variables; Reactive demands; Probability distribution functions; Mathematical formulation; Two-stage stochastic model; Multiperiod mixed-integer convex model; Risk mitigation; Investment cost minimisation; CIGRE-32 electric power system; Optimisation solver CPLEX; AMPL